The Effects of Adverse Childhood Experiences on Internalizing Versus Externalizing Outcomes. (April 2019) - Muniz, Caitlyn N.; Fox, Bryanna; Miley, Lauren N.; Delisi, Matt; Cigarran, Gerald P.; Birnbaum, Aliya
This study examines the effects of adverse childhood experiences (ACEs) on the risk of internalizing or externalizing outcomes among juveniles. While myriad research has investigated the impacts of ACEs on internalizing and externalizing outcomes, it is unclear whether ACEs have a stronger link to one outcome over the other when controlling for other factors. Using a sample of 30, 909 youth who exclusively exhibited internalizing ( n = 1, 030) or externalizing problems ( n = 29, 879), regression techniques and propensity score matching were utilized to evaluate the impact of each ACE on the risk of internalizing versus externalizing outcomes. Results indicate that the most pertinent factor for predicting externalized problems is emotional abuse. Household member incarceration, physical abuse, emotional neglect, and household violence or substance abuse also predicted externalizing outcomes. Sexual abuse was the only ACE predictive of internalizing, while physical neglect and parental mental illness did not have a correlation with either outcome.